Health-Related Behaviors Among School-Aged Children and Adolescents During the Spanish Covid-19 Confinement - López-Bueno, Rubén; López-Sánchez, Guillermo F.; Casajús, José A.; Calatayud, Joaquín; Gil-Salmerón, Alejandro; Grabovac, Igor; Tully, Mark A.; Smith, Lee (Frontiers in pediatrics, 2020)
In response to the coronavirus disease 2019 (Covid-19) world pandemic, affected countries such as Spain enacted measures comprising compulsory confinement as well as restrictions regarding free movement. Such measures likely influence children's and adolescents' lifestyles. Our study aimed to investigate the impact that the Covid-19 confinement has on health-related behaviors (HRBs) among Spanish children and adolescents. An online survey was administered to 516 parents to collect data about 860 children and adolescents (49.2% girls) aged between 3 and 16 years in relation to physical activity, screen exposure, sleep time, and fruit and vegetable consumption during the Covid-19 confinement. Respectively, -paired test and -test between groups served to check differences between HRBs levels before and during the confinement as well as between strict and relaxed confinement. Significant differences were found for a reduction of weekly minutes of physical activity during the confinement (-102.5, 159.6) ( < 0.001), an increase of daily hours of screen exposure (2.9, 2.1) ( < 0.001), and a reduction of daily fruit and vegetable consumption (-0.2, 1.6) ( < 0.001). Sleep time showed a significant difference between strict and relaxed confinement (-0.3, 0.1) ( < 0.05), whereas binomial logistic regression adjusted for covariates (age, sex, education of the parents, siblings, current condition, exposure to Covid-19, and previous health risk behavior) showed significantly lower odds for screen exposure risk behavior with relaxed confinement (OR 0.60, 95%CI 0.40-0.91). The present study suggests that Covid-19 confinement reduced physical activity levels, increased both screen exposure and sleep time, and reduced fruit and vegetable consumption. Therefore, most HRBs worsened among this sample of Spanish children and adolescents. Closure of schools, online education, and the lack of policies addressing the conciliation between labor and family life could have played an important role in HRBs worsening among pupils, which might be mitigated with adequate conciliation policies, parental guidance, and community support.